Effect of Drying Method in the Maintenance of Bioactive Compounds and Antioxidant Activity of Feijoa Pulp (Acca sellowiana) - Buratto, Ana Paula; Carpes, Solange Teresinha; Pereira, Edimir Andrade; Diedrich, Camila; Oldoni, Tatiane Luiza Cadorin; da Silva, Leticia Dangui (Orbital: The Electronic Journal of Chemistry, 2019)
The aim of this work was to evaluate the bioactive compounds contents and the antioxidant activity preserved in the obtained powders of dehydrated feijoa pulp after two drying methods applied: Spray drying and Freeze-drying methods. Ascorbic acid, total phenolic and total flavonoids content, antioxidant activity (by DPPH, ABTS and FRAP methods) were determined and the obtained data were evaluated using ANOVA and Tukey test (p < 0.05). Spray drying method produced powders with higher amounts of total phenolic and total flavonoid contents, while Freeze-drying method presented higher amounts of ascorbic acid and higher antioxidant activity. Both applied methods were effective in maintaining the antioxidant properties of Feijoa fruits. DOI: http://dx.doi.org/10.17807/orbital.v11i6.1223